Studi Kelayakan Pemasangan Stasiun Pengisian Kendaraan Listrik Umum (SPKLU) di Wilayah Kota Makassar - Jaenuddin, Muhammad Ridwan; Prabowo, Eri; Jaenuddin, Nurfitri (Syntax Literate, 2025)
The rapid advancement of Electric Vehicles as an environmentally friendly alternative drives the need for the provision of an effective and adequate charging network. This study aims to assess the economic feasibility of developing Public Electric Vehicle Charging Stations (SPKLU) in the Makassar City area using key financial indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period. The study identifies the feasibility levels of various SPKLU technology categories, namely Standard Charging, Fast Charging, and Ultra Fast Charging. The analysis results show that the development of Standard and Fast Charging SPKLU categories, especially those located at ULP Mattoanging and UP3 Makassar Selatan, are economically feasible with positive NPV values, IRR exceeding the 10% discount rate, and a Payback Period of less than five years. Conversely, the Ultra Fast Charging category SPKLU has not shown short-term economic feasibility. The main factors influencing economic feasibility include utilization rates, initial investment costs, strategic location, operational cost efficiency, and electricity tariffs. This study recommends prioritizing the development of Fast Charging SPKLU at ULP Mattoanging as the most potential investment unit with an NPV of IDR 108 million and an IRR of 45%. The findings provide important contributions for policymaking to accelerate Electric Vehicle infrastructure development in Indonesia, particularly in the context of electricity business development and sustainable energy transformation.